Publication and Dating of Parts IV–VII of Brauer & Bergenstamm’s Die Zweiflügler des Kaiserlichen Museums zu Wien (1889–1894) - Evenhuis, Neal L. (Zootaxa, 2014)
Based on new evidence, the dates of publication of the journal and separate versions of parts IV–VII of Brauer & Bergenstamm’s Die Zweiflügler des Kaiserlichen Museums zu Wien are given, correcting those dates previously published.